How can relational, decolonial and feminist approaches inform the EU bioeconomy? - Ramcilovic-Suominen, Sabaheta; Giuntoli, Jacopo; Oliver, Tom; Mehta, Lyla (Springer Nature, 2025)
In this commentary we argue that, to transform the bioeconomy sectors towards ecologically less harmful and socially fairer outcomes, the bioeconomy policy project must be questioned, re-politicised and fundamentally reframed and reinvented. We firstly identify some of the main root causes for continuity of extractivism and injustices in the bioeconomy policy and, more broadly, in the green transition (“Root causes of today’s socioecological crises and why they matter for the EU bioeconomy project” section). Secondly, we outline the largely neglected ideas and concerns emerging from relational, feminist and decolonial approaches and perspectives (“Moving beyond growth while enabling marginalised voices, knowledges, and practices that nurture web of life and wellbeing for all” section). Finally, we compile a list of 11 actions and 47 suggestions for decisionmakers, practitioners and academics to contemplate on how to cocreate bioeconomies founded on ethics of care, relationality and socioecological justice. Ultimately, the aim is to reject socioecological domination, extractivism and exploitation and foster collective wellbeing for all beings, human and other-than-human.
Keywords: EU bioeconomy; colonialism-capitalism; extractivism; decoloniality; relationality; feminist approaches